Analisis Pengaruh Communication and Interaction dan PWE (Physical Work Environment) terhadap IOC (Innovative Organizational Culture) yang Dimediasi oleh Employee Performance pada Karyawan Gen Z Perusahaan Startup di Jakarta Pusat - Rosalinda, Ana; Emilisa, Netania; Saputra, Gavrila Indra; Rahma, Nida Nayla (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Startups in Jakarta are facing intense competition and a workforce dominated by Generation Z, presenting new challenges in cultivating an innovative organizational culture (IOC). This study investigates the influence of Communication and Interaction and the Physical Work Environment (PWE) on IOC, with Employee Performance serving as a mediating variable. The research aims to examine whether strong communication practices and a conducive physical work environment can enhance employee performance, ultimately fostering innovation within organizational culture. A quantitative correlational approach was employed, with data collected from 117 Generation Z employees (aged 20–30) working at startup companies in Central Jakarta. The survey was administered online, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that both Communication and Interaction and PWE have significant positive effects on Employee Performance. Furthermore, Employee Performance significantly influences IOC and mediates the relationship between both independent variables and IOC. The findings highlight the need for startups to invest in open, technology-driven communication systems and well designed, ergonomic workspaces to optimize Gen Z performance and cultivate a sustainable innovative culture. This study contributes to organizational behavior research by emphasizing the mediating role of employee performance and addressing a contextual gap in the literature, particularly in the startup ecosystem of Indonesia.